Deep Eutectic Solvents as Active Pharmaceutical Ingredient Delivery Systems in the Treatment of Metabolic Related Diseases - Huang, Cixin; Chen, Xiunian; Wei, Chao; Wang, Hongwei; Gao, Hua (Frontiers in Pharmacology, 2021)
Metabolic related diseases such as cancer, diabetes mellitus and atherosclerosis are major challenges for human health and safety worldwide due to their associations with high morbidity and mortality. It is of great significance to develop the effective active pharmaceutical ingredient (API) delivery systems for treatment of metabolic diseases. With their unique merits like easy preparation, high adjustability, low toxicity, low cost, satisfactory stability and biodegradation, deep eutectic solvents (DESs) are unarguably green and sustainable API delivery systems that have been developed to improve drug solubility and treat metabolic related diseases including cancer, diabetes mellitus and atherosclerosis. Many reports about DESs as drug delivery systems in the therapy of cancer, diabetes mellitus and atherosclerosis exist but no systematic overview of these results is available, which motivated the current work.